Pengaruh Kepemimpinan Transformasional, Budaya Organisasi, Perilaku Organisasi Terhadap Kinerja Karyawan (Pada PT. Inkor Bola Pacific Pasuruan) - Lista Sefti Anggraeni; Muhammad Ridwan Basalamah; Eka Farida (UNIVERSITAS ISLAM MALANG, 2021)
Abstract This study aims the effect of Transformational Leadership, Organizational Culture, Organizational Behavior have on Employee Performance. Studies at PT. Inkor Bola Pacific in the Pasuruan Regency area. In this study amounted to 70 respondents. The sampling technique used non-probability sampling technique. The sampling method is, employees who work at PT. Pasuruan Pacific Football Inkor. To find out the data that will be studied later, this study uses a questionnaire to find out more about the opinions of employees by filling in the statements that have been attached to the questionnaire. In addition, this research uses SPSS measuring instrument to test data in the form of instrument testing, multiple linear regression analysis, classical assumption testing, and hypothesis testing. From this study resulted in several conclusions stating that the variables of Transformational Leadership, Organizational Culture, Organizational Behavior have a joint effect on the performance of employees of PT. Pasuruan Pacific Football Inkor. While partially transformational leadership affects employee performance, organizational culture affects employee performance, and organizational behavior affects employee performance.Keywords: Influence, Transformational Leadership, Organizational Culture, Organizational Behavior, Employees